ABOUT FORMING OF PROFESSIONAL INFORMATIVE CULTURE OF FUTURE TEACHER OF MATHEMATICS - Shishko Л.С.; Chernenko І.Є. (Journal of Information Technologies in Education (ITE), 2010)
The problem of preparation of future teachers of mathematics for general school from the point of methodical and organizational questions of forming of professional informative culture of future teacher of mathematics is considered in the аrticle.